Inadequacy of the measures implemented by the State to guarantee access to euthanasia in Colombia - Ramos-Ortega, Mayra Alejandra; Tirado Álvarez, María Margarita (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Euthanasia in Colombia, understood as the fundamental right to die with dignity, has been developed jurisprudentially by the Constitutional Court since 1997; Since then, several pronouncements have emerged from the same corporation in this regard, which urge the adoption of legal measures to incorporate it into the national regulatory body. However, even the Congress of the Republic has not regulated the matter, being the Ministry of Health and Social Protection that, in compliance with the order imposed by the Court, has issued some guidelines about the application of the procedure, plus the lack of law has caused difficulties for its complete implementation. That is why, through a non-experimental qualitative study with documentary review, this article aims to address the insufficiency of the measures that the State has implemented up to now to protect the right to die with dignity and what have been the issues that have hindered the application of euthanasia, resulting in a clear legal insecurity that leads to patients suffering from terminal illnesses, not being able to effectively access euthanasia.